Videos: contribution to the practical teaching in the disciplinary area of Orthoptics at ESTeSL - Miguel, Ângela (2021)
Introduction – Technological development leads to the acquirement of new learning methods which are complementary to the traditional ones. With mobile learning emerging as a distance education method, mobile devices are used to learn. In the field of Orthoptics and Science, we have not found yet enough credible visual content in the Portuguese language. Objectives – Provide students videos executing several clinical evaluation exams, which will increase the learning process curve in the clinical practice of assessing ocular motility and binocular vision.Methods – Quantitative, observational, and prospective descriptive study with a sample of 108 students (n=108). Recording of thirteen videos about Orthoptics clinical practice and posteriorly publishment in the platform YouTube. To assess students’ perception of watching videos as a facilitating contribution to the practical learning process, a previously validated poll was given to the students of the Orthoptics and Vision Sciences Degree at Escola Superior de Tecnologia da Saúde de Lisboa. Results and Discussion – Most of the sample’s gender was female (80.56%) where the age ranged from 18 to 37 years old, with an average of 21.12±2.96; 29 answers from the degree’s 1st year (26.85%); 26 from the 2nd year (24.07%); 18 from the 3rd year (16.67%); 35 from the 4th year (32.41%). The respondents consider the videos to be a complementary way of studying; 98.14% (n=106) answered that the videos stimulate motivation and interest; 96.30% (n=104) reported acquiring knowledge faster through videos; 92.59% (n=100) have the interest to use it while studying. Conclusion – The videos are a complement to traditional individual study.There is also a concern in broadening the YouTube channel to other areas in the visual sciences, including examinations to individuals with visual pathologies.